Effects of drought stress on seed germination, growth and physiological traits of dwarf wheats at seedling and maturity stage - Shan DUAN; Peipei AN; Xiaoyan ZHANG; Xuezhen LIU; Jia ZHANG; Xiaoyu WANG; Lei XING; Julian ZHAO (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
Water deficiency is a major constraint in wheat productivity in arid and semi-arid areas. Height-reducing genes, such as Rht decrease plant height while enhancing yield. However, their benefits in arid environments are poorly understood. We evaluate the effects of drought induced by 10% and 20% polyethylene glycol (PEG) 6000, and water shortage on seed germination, growth, physiological traits, and agronomic traits of 12 wheat varieties (11 dwarf and 1 tall) at seedling and maturity stages. Several indicators (germination energy, germination index, root number, and maximum root, coleoptile, and shoot lengths) in some varieties were promoted by 10% PEG-6000, however, all indicators were inhibited at 20% PEG-6000. A positive and significant correlation occurred between shoot fresh weight and both shoot dry weight and relative water content. Shoot fresh weight explained most (positive) variation in principal component analysis (PC1), and peroxidase activity was the least (negative) variation. Plant height and yield components decreased in all wheat varieties with moderate and severe drought stress. A drought resistance coefficient revealed rht (Langdon) was most drought resistant at 10% PEG-6000, Rht2 (Xinong 223) at 20% PEG-6000, and Rht8 (Jinmai 47) at both moderate and severe drought stress. These findings can be used to identify appropriate wheat varieties to cultivate in water-deficient areas.